High-Performance Steel Bars and Fibers as Concrete Reinforcement for Seismic-Resistant Frames - Andres Lepage; Hooman Tavallali; Santiago Pujol; Jeffrey M. Rautenberg (Advances in Civil Engineering)
Experimental data are presented for six concrete specimens subjected to displacement reversals. Two specimens were reinforced longitudinally with steel bars Grade 410 (60 ksi), two with Grade 670 (97 ksi), and two with Grade 830 (120 ksi). Other experimental variables included axial load (0 or 0.2 fc′  Ag) and volume fraction of hooked steel fibers (0 or 1.5%). All transverse reinforcement was Grade 410, and the nominal concrete compressive strength was 41 MPa (6 ksi). The loading protocol consisted of repeated cycles of increasing lateral displacement reversals (up to 5% drift) followed by a monotonic lateral push to failure. The test data indicate that replacing conventional Grade-410 longitudinal reinforcement with reduced amounts of Grade-670 or Grade-830 steel bars did not cause a decrease in usable deformation capacity nor a decrease in flexural strength. The evidence presented shows that the use of advanced high-strength steel as longitudinal reinforcement in frame members is a viable option for earthquake-resistant construction.